Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1126/scisignal.aaw4956
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-based direct threat sensing by the stress-activated protein kinase Hog1

Abstract: The yeast stress-activated protein kinase Hog1 is best known for its role in mediating the response to osmotic stress, but it is also activated by various mechanistically distinct environmental stressors, including heat shock, endoplasmic reticulum stress, and arsenic. In the osmotic stress response, the signal is sensed upstream and relayed to Hog1 through a kinase cascade. Here, we identified a mode of Hog1 function whereby Hog1 senses arsenic through a direct physical interaction that requires three conserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…Because we have found that some cysteine residues in proteins are specifically targeted by MAs(III) (Lee and Levin, 2018;2019), we examined whether Hog1 is modified by As(III), or by MAs(III). Pre-treatment of wild-type cells with either As(III) or As(V) diminished As-biotin binding to Hog1 (Figure 2G).…”
Section: Hog1 Is Modified By As(iii)mentioning
confidence: 99%
See 2 more Smart Citations
“…Because we have found that some cysteine residues in proteins are specifically targeted by MAs(III) (Lee and Levin, 2018;2019), we examined whether Hog1 is modified by As(III), or by MAs(III). Pre-treatment of wild-type cells with either As(III) or As(V) diminished As-biotin binding to Hog1 (Figure 2G).…”
Section: Hog1 Is Modified By As(iii)mentioning
confidence: 99%
“…However, some As-biotin binding to Hog1 remained even in the Hog1-3C/S mutant form. Guerra-Moreno et al (2019) reported recently that Hog1 becomes modified on three cysteine residues --Cys156, Cys161, and Cys205 in response to As(III) treatment. Because we had not included Cys161 in our initial analysis, we added the Cys161Ser mutation to the hog1-3C/S allele, yielding hog1-4C/S.…”
Section: Hog1 Is Modified By As(iii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, if and/or what alternative signaling is activated in yeast upon IRE1 modification remains to be elucidated. Hog1, the homologous yeast p38 MAP kinase, is activated by arsenite exposure [ 117 , 118 ]; yet, activation does not require the IRE1 cysteine [ 117 ]. The ultimate transcriptional output is also bound to be different.…”
Section: Er Targets Of H 2 Omentioning
confidence: 99%
“…Additionally, Yap8 is phosphorylated by the Hog1 kinase during As(III) stress and this phosphorylation contributes to efficient induction of ACR2 and ACR3 expression by an unknown mechanism (Guerra-Moreno et al . 2019 ). Full induction of ACR2 and ACR3 expression also involves coactivator complexes and chromatin remodeling factors (Menezes et al .…”
Section: Introductionmentioning
confidence: 99%